Qualitative study on mental health and well-being of Syrian refugees and their coping mechanisms towards integration in the UK - Maxwell J F Cooper; Priyamvada Paudyal; Mais Tattan (BMJ Open)
Objective This study aimed to explore the mental well-being of Syrian refugees and identify their coping mechanisms and pathways towards integration into new communities.Design Qualitative study using in-depth semi-structured interviews.Setting and participants Adult Syrian refugees (>18 years old) currently residing in South East of England.Results 12 participants (3 women and 9 men) took part in the study, all were born in Syria and the majority (n=9) were over 45 years of age. Our findings show that Syrian refugees face constant challenges as they try to integrate into a new society. Loss of and separation from loved ones as well as the nostalgia for the homeland were often cited as a source of psychological distress that created an overwhelming sense of sadness. Participants reported that they struggled for connectedness due to cultural difference and the problematic nature of rapidly formed migrant communities in their new setting. They believed in ‘being their own doctor’ and turning to faith, ritual and nature for healing and comfort. Taboo and stigma around mental health and language barriers were cited as barriers to accessing mental healthcare services.Conclusion Past experiences and present challenges frame Syrian refugees’ sense of well-being, impact use of healthcare and risk future mental health problems. It is hoped that this study will act as a catalyst for further research on this vulnerable group to promote integration, community support and culturally sensitive mental health services.